4D cardiac magnetic resonance imaging, 4D and 2D transthoracic echocardiography: a comparison of in-vivo assessment of ventricular function in rats - Stegmann, Hedwig; Bäuerle, Tobias; Kienle, Katharina; Dittrich, Sven; Alkassar, Muhannad (Laboratory Animals, 2019)
Preclinical cardiovascular research is the foundation of our understanding and broad knowledge of heart function and cardiovascular disease. Reliable cardiac imaging modalities are the basis for applicable results. Four-dimensional cardiac magnetic resonance (4D CMR) has been set as the gold standard for in-vivo assessment of ventricular function in rodents. However, technical improvements in echocardiography now allow us to image the whole heart, which makes four-dimensional echocardiography (4DE) a possible alternative to 4D CMR. To date, no study has systematically assessed 4DE in comparison with 4D CMR in rats. In total we studied 26 juvenile Sprague-Dawley rats (Crl: CD (SD) IGS). Twenty rats underwent echocardiographic imaging (2D and 4D) and 4D CMR. Five of those rats underwent a ligation of the superior and inferior vena cava to reduce the cardiac inflow as a disease model. Six additional rats were used to assess reproducibility of echocardiography and underwent three echocardiographic examinations. 4D CMR was performed on a 7T scanner; 2D and 4D echocardiography was conducted using a 40 MHz transducer. Correlation between 4D CMR, 4DE and 2DE for left-ventricular ejection fraction (LVEF) was assessed. An excellent correlation was observed between 4DE and 4D CMR (r = 0.95, p < 0.001). Correlation of 2DE and 4D CMR was weak (r = 0.57, p < 0.01). 4DE provides results that are equally precise as 4D CMR and highly reproducible with less technical effort than 4D CMR.
CRIS-Team Scopus Importer:2019-05-09
Keywords: cardiac magnetic resonance; echocardiography; four-dimensional cardiac imaging; left ventricular function; rat

A new approach of three-dimensional guidance in paediatric cath lab: segmented and tessellated heart models for cardiovascular interventions in CHD - Ehret, Nicole; Alkassar, Muhannad; Dittrich, Sven; Cesnjevar, Robert; Ruffer, Andre; Uder, Michael; Rompel, Oliver; Hammon, Matthias; Glöckler, Martin (Cardiology in the Young, 2018)
BACKGROUND: Optimal imaging is essential for catheter-based interventions in CHD. The three-dimensional models in volume-rendering technique currently in use are not standardised. This paper investigates the feasibility and impact of novel three-dimensional guidance with segmented and tessellated three-dimensional heart models in catheterisation of CHD. In addition, a nearly radiation-free two- to three-dimensional registration and a biplane overlay were used.Methods and resultsWe analysed 60 consecutive cases in which segmented tessellated three-dimensional heart models were merged with live fluoroscopy images and aligned using the tracheal bifurcation as a fiducial mark. The models were generated from previous MRI or CT by dedicated medical software. We chose the stereo-lithography format, as this promises advantage over volume-rendering-technique models regarding visualisation. Prospects, potential benefits, and accuracy of the two- to three-dimensional registration were rated separately by two paediatric interventionalists on a five-point Likert scale. Fluoroscopy time, radiation dose, and contrast dye consumption were evaluated. Over a 10-month study period, two- to three-dimensional image fusion was applied to 60 out of 354 cases. Of the 60 catheterisations, 73.3% were performed in the context of interventions. The accuracy of two- to three-dimensional registration was sufficient in all cases. Three-dimensional guidance was rated superior to conventional biplane imaging in all 60 cases. We registered significantly smaller amounts of used contrast dye (p<0.01), lower levels of radiation dose (p<0.02), and less fluoroscopy time (p<0.01) during interventions concerning the aortic arch compared with a control group. CONCLUSIONS: Two- to three-dimensional image fusion can be applied successfully in most catheter-based interventions of CHD. Meshes in stereo-lithography format are accurate and base for standardised and reproducible three-dimensional models.
EVALuna2:34698

A Transmural Path Model Improves the Definition of the Orthotropic Tissue Structure in Heart Simulations - Holz, David; Duong, Minh Tuan; Martonová, Denisa; Alkassar, Muhannad; Leyendecker, Sigrid (Journal of Biomechanical Engineering-Transactions of the Asme, 2021)
In the past decades, the structure of the heart, human as well as other species, has been explored in a detailed way, e.g., via histological studies or diffusion tensor magnetic resonance imaging. Nevertheless, the assignment of the characteristic orthotropic structure in a patient-specific finite element model remains a challenging task. Various types of rule-based models, which define the local fiber and sheet orientation depending on the transmural depth, have been developed. However, the correct assessment of the transmural depth is not trivial. Its accuracy has a substantial influence on the overall mechanical and electrical properties in rule-based models. The main purpose of this study is the development of a finite element-based approach to accurately determine the transmural depth on a general unstructured grid. Instead of directly using the solution of the Laplace problem as the transmural depth, we make use of a well-established model for the assessment of the transmural thickness. It is based on two hyperbolic first-order partial differential equations for the definition of a transmural path, whereby the transmural thickness is defined as the arc length of this path. Subsequently, the transmural depth is determined based on the position on the transmural path. Originally, the partial differential equations were solved via finite differences on structured grids. In order to circumvent the need of two grids and mapping between the structured (to determine the transmural depth) and unstructured (electromechanical heart simulation) grids, we solve the equations directly on the same unstructured tetrahedral mesh. We propose a finite-element-based discontinuous Galerkin approach. Based on the accurate transmural depth, we assign the local material orientation of the orthotropic tissue structure in a usual fashion. We show that this approach leads to a more accurate definition of the transmural depth. Furthermore, for the left ventricle, we propose functions for the transmural fiber and sheet orientation by fitting them to literature-based diffusion tensor magnetic resonance imaging data. The proposed functions provide a distinct improvement compared to existing rules from the literature.<br

Characterisation of passive mechanical properties in healthy and infarcted rat myocardium - Martonová, Denisa; Alkassar, Muhannad; Seufert, Julia; Holz, David; Duong, Minh Tuan; Reischl, Barbara; Friedrich, Oliver; Leyendecker, Sigrid (conference, GAMM Annual Meeting, 2021)

Cinematic Rendering in Mixed-Reality Holograms: A New 3D Preoperative Planning Tool in Pediatric Heart Surgery - Gehrsitz, Pia; Rompel, Oliver; Schoeber, Martin; Cesnjevar, Robert; Purbojo, Ariawan; Uder, Michael; Dittrich, Sven; Alkassar, Muhannad (Frontiers in Cardiovascular Medicine, 2021)
Cinematic rendering (CR) is based on a new algorithm that creates a photo-realistic three-dimensional (3D) picture from cross-sectional images. Previous studies have shown its positive impact on preoperative planning. To date, CR presentation has only been possible on 2D screens which limited natural 3D perception. To depict CR-hearts spatially, we used mixed-reality technology and mapped corresponding hearts as holograms in 3D space. Our aim was to assess the benefits of CR-holograms in the preoperative planning of cardiac surgery. Including 3D prints allowed a direct comparison of two spatially resolved display methods. Twenty-six patients were recruited between February and September 2019. CT or MRI was used to visualize the patient's heart preoperatively. The surgeon was shown the anatomy in cross-sections on a 2D screen, followed by spatial representations as a 3D print and as a high-resolution hologram. The holographic representation was carried out using mixed-reality glasses (HoloLens (R)). To create the 3D prints, corresponding structures were segmented to create STL files which were printed out of resin. In 22 questions, divided in 5 categories (3D-imaging effect, representation of pathology, structure resolution, cost/benefit ratio, influence on surgery), the surgeons compared each spatial representation with the 2D method, using a five-level Likert scale. The surgical preparation time was assessed by comparing retrospectively matched patient pairs, using a paired t-test. CR-holograms surpassed 2D-monitor imaging in all categories. CR-holograms were superior to 3D prints in all categories (mean Likert scale 4.4 +/- 1.0 vs. 3.7 +/- 1.3, P < 0.05). Compared to 3D prints it especially improved the depth perception (4.7 +/- 0.7 vs. 3.7 +/- 1.2) and the representation of the pathology (4.4 +/- 0.9 vs. 3.6 +/- 1.2). 3D imaging reduced the intraoperative preparation time (n = 24, 59 +/- 23 min vs. 73 +/- 43 min, P < 0.05). In conclusion, the combination of an extremely photo-realistic presentation via cinematic rendering and the spatial presentation in 3D space via mixed-reality technology allows a previously unattained level of comprehension of anatomy and pathology in preoperative planning.
CRIS-Team WoS Importer:2021-03-12

Comparison of stress and stress–strain approaches for the active contraction in a rat cardiac cycle model - Martonová, Denisa; Holz, David; Seufert, Julia; Duong, Minh Tuan; Alkassar, Muhannad; Leyendecker, Sigrid (Journal of Biomechanics, 2022)
In the last decades, different strategies to model the active electromechanically coupled behaviour of the cardiac tissue were proposed in order to simulate electromechanics of the heart under healthy and pathological conditions. The main objective of this work is to compare two approaches for modelling the active contraction during the electromechanically coupled rat cardiac cycle —- the stress and the stress–strain approach. Firstly, a cylindrical benchmark is considered and secondly, for a generic model of a rat left ventricle, a simulation including the Windkessel model, excitation via Purkinje fibre network and mechano-electrical feedback is performed. The model is calibrated with experimental data for rats, partly from own measurements via cardiac ultrasound, partly from the literature. Further, possibilities to reach higher ejection fractions are discussed and considered for an exemplary rat left ventricle. Within each approach, we observe regionally different active stresses and fibre stretches. Moreover, the transmural active stress and fibre stretch distribution is influenced by the pressure load on the endocardial surface. The active stress approach is not sensitive to the fibre stretch and transmurally varying fibre stretch in the left ventricular domain is observed. The active stress–strain approach leads to transmurally more homogeneous fibre stretch at the end-systolic state.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Active stress; Cardiac cycle; Cardiac electromechanics; Finite element method; Rat left ventricle

Computational model of a rat left ventricle - Holz, David; Duong, Minh Tuan; Alkassar, Muhannad; Dittrich, Sven; Leyendecker, Sigrid (8th Summer School on Biomechanics, from Protein to Tissue to Organ: Modeling and Computation, 2018)

Computational study of ventricular fibrillation by considering a strongly coupled electromechanical rat heart model - Holz, David; Duong, Minh Tuan; Alkassar, Muhannad; Dittrich, Sven; Leyendecker, Sigrid (Procc. App. Math. Mech. (PAMM), 2019)

Discontinuous Galerkin-based approach to define orthotropic tissue structure in computational heart models - Holz, David; Duong, Minh Tuan; Martonová, Denisa; Alkassar, Muhannad; Leyendecker, Sigrid (conference, International Conference on Computational Biomechanics, 2021)

Evaluating Cardiac Lateralization by MRI to Simplify Estimation of Cardiopulmonary Impairment in Pectus Excavatum - Abu-Tair, Tariq; Turial, Salmai; Willershausen, Ines; Alkassar, Muhannad; Staatz, Gundula; Kampmann, Christoph (Diagnostics, 2023)
Background: The severity of pectus excavatum is classified by the Haller Index (HI) and/or Correction Index (CI). These indices measure only the depth of the defect and, therefore, impede a precise estimation of the actual cardiopulmonary impairment. We aimed to evaluate the MRI-derived cardiac lateralization to improve the estimation of cardiopulmonary impairment in Pectus excavatum in connection with the Haller and Correction Indices. Methods: This retrospective cohort study included a total of 113 patients (mean age = 19.03 ± 7.8) with pectus excavatum, whose diagnosis was verified on cross-sectional MRI images using the HI and CI. For the development of an improved HI and CI index, the patients underwent cardiopulmonary exercise testing to assess the influence of the right ventricle’s position on cardiopulmonary impairment. The indexed lateral position of the pulmonary valve was utilized as a surrogate parameter for right ventricle localization. Results: In patients with PE, the heart’s lateralization significantly correlated with the severity of pectus excavatum (p ≤ 0.001). When modifying HI and CI for the individual’s pulmonary valve position, those indices are present with greater sensitivity and specificity regarding the maximum oxygen-pulse as a pathophysiological correlate of reduced cardiac function (χ2 10.986 and 15.862, respectively). Conclusion: The indexed lateral deviation of the pulmonary valve seems to be a valuable cofactor for HI and CI, allowing for an improved description of cardiopulmonary impairment in PE patients.
CRIS-Team Scopus Importer:2023-03-24
Keywords: cardiac lateralization; cardiopulmonary exercise testing; chest wall deformity; correction index; Haller index; pectus excavatum

Growth of hypoplastic mitral valves in hypoplastic left heart complex and similar constellations after anatomical left superior vena cava correction - Cesnjevar, Robert; Harig, Frank; Dietz, Moritz; Alkassar, Muhannad; Waellisch, Wolfgang; Rueffer, André; Dittrich, Sven; Purbojo, Ariawan (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES: Left superior vena cava (LSVC)-related obstruction of mitral inflow is a rare finding in patients with complex cardiac anomalies like hypoplastic left heart complex. We report our experience by establishing a left superior to right superior caval vein continuity (innominate vein creation by direct LSVC-right superior vena cava end-to-side-anastomosis), and coronary sinus unroofing if indicated for LSVC-related mitral inflow obstruction. METHODS: Nineteen patients (median age: 1.0 ± 0.3 years; range: 7 days-4.8 years) underwent anatomical correction of LSVC without the use of foreign material in conjunction with repair or palliation of congenital anomalies in a single centre between April 2015 and November 2019. Indications for the procedure were LSVC-related obstruction of left ventricular inflow due to a dilated coronary sinus. Additional procedures included mitral (n = 7) or atrioventricular (n = 3) valve surgery, right ventricular to pulmonary artery conduit (n = 3), first stage palliation (n = 3) or biventricular repair (n = 5) of hypoplastic left heart complex. Three patients needed secondary mitral valve replacement (n = 3). RESULTS: All LSVC or coronary sinus-related obstructions were effectively relieved. No patient died early, 2 patients died late after the procedure. One patient needed stenting of the superior vena cava below the unobstructed cephalad vein anastomosis at the former right superior vena cava-cannulation-site. Follow-up was complete and demonstrated an 89.5% survival after 2.5 ± 0.4 years. Innominate vein patency was 100% documented by echocardiography (n = 19), cardiac catheterization (n = 6) or both. Mean mitral valve z-scores before the operation were -1.7 ± 0.2 (range -3.8 to 0.3) and increased to 0.7 ± 0.2 (range -0.7 to 1.9) after LSVC repair. CONCLUSIONS: Anatomical correction by surgical creation of an innominate vein is an effective method to relieve LSVC-related obstructions and promotes mitral valvar growth. Mitral ring sizes were at least normalized after surgery at the time of discharge. Further prospective follow-up studies to evaluate the growth potential of left-sided heart structures by reporting cardiac z-scores are needed to evaluate the true impact of coronary sinus unroofing.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Congenital heart disease; Hypoplastic left heart complex; Left superior vena cava; Mitral valve growth; Mitral valve z-score

Influence of passive mechanical properties in healthy and infarcted rat myocardium on the cardiac cycle - Martonová, Denisa; Alkassar, Muhannad; Seufert, Julia; Holz, David; Duong, Minh Tuan; Reischl, Barbara; Friedrich, Oliver; Leyendecker, Sigrid (Proc. Appl. Math. Mech. (PAMM), 2021)

Interaction of the mechano-electrical feedback with passive mechanical models on a 3D rat left ventricle: a computational study - Duong, Minh Tuan; Holz, David; Alkassar, Muhannad; Dittrich, Sven; Leyendecker, Sigrid (Frontiers in Physiology, 2019)
In this paper, we are investigating the interaction between different passive material models and the mechano-electrical feedback (MEF) in cardiac modelling. Various types of passive mechanical laws (nearly incompressible/compressible, polynomial/exponential-type, transversally isotropic/orthotropic material models) are integrated in a fully coupled electromechanical model in order to study their specific influence on the overall MEF behaviour. Our computational model is based on a three-dimensional (3D) geometry of a healthy rat left ventricle reconstructed from magnetic resonance imaging (MRI). The electromechanically coupled problem is solved using a fully implicit finite element-based approach. The effects of different passive material models on the MEF are studied with the help of numerical examples. It turns out that there is a significant difference between the behaviour of the MEF for compressible and incompressible material models. Numerical results for the incompressible models exhibit that a change in the electrophysiology can be observed such that the transmembrane potential (TP) is unable to reach the resting state in the repolarisation phase and this leads to non-zero relaxation deformations. The most significant and strongest effects of the MEF on the rat cardiac muscle response are observed for the exponential passive material law.<br
Keywords: Electromechanics; Excitation-contraction; Mechano-electrical feedback; passive mechanics; rat left ventricle; FEM; Compressible; Incompressible; Exponential; Polynomial; Orthotropic; Transversely isotropic

Long-Term Results after Fallot Repair - Kleinöder, Jonas; Purbojo, Ariawan; Blumauer, Robert; Cuomo, Michela; Alkassar, Muhannad; Dittrich, Sven; Cesnjevar, Robert (Thoracic and Cardiovascular Surgeon, 2022)
Background The aim of this study was to evaluate the long-term outcome and freedom from pulmonary valve replacement (PVR) after initial repair of tetralogy of Fallot (TOF). Patients and Methods The cohort of 306 patients treated between 1980 and 2017 was divided into anatomical subgroups according to the diagnosis of TOF-pulmonary stenosis, TOF-pulmonary atresia and TOF-double outlet right ventricle. Patients were treated with transannular patch (TAP), valve sparing repair (VSR), or conduits from the right ventricle to the pulmonary arteries (RVPA conduits). Results There were 21 deaths (6.9%), 14 being hospital deaths (4.6%) after primary correction and four deaths (1.3%) occurred after PVR. One patient died after a non-cardiac operation (0.3%). There were two late deaths (0.7%). During the past 12 years no early mortality has been observed. Ninety-one patients (30.4%) received PVR after a median of 12.1 +/- 7.0 years with an early mortality of 4.4% ( n = 4) and no late mortality. A significant difference in freedom from reoperation after TAP, VSR, and RVPA-conduits could be identified. Multivariate analysis displayed transannular repair ( p = 0.016), primary palliation ( p <0.001), the presence of major aortopulmonary collateral arteries (MAPCA; p = 0.023), and pulmonary valve Z -scores < - 4.0 ( p = 0.040) as significant risk factors for PVR. Conclusion TOF repair has a beneficial long-term prognosis with low morbidity and mortality. Pulmonary valve Z -scores < - 4.0, transannular repair, and presence of MAPCAs are associated with earlier PVR. Non-VSRs and TOF-pulmonary atresia lead to earlier reoperation but have no negative impact on survival.
CRIS-Team WoS Importer:2022-07-29

Modelling cardiac mechanics and electrophysiology of a rat left ventricle: A case study. - Duong, Minh Tuan; Wenger, Theresa; Herrnböck, Ludwig; Ach, Theresa; Holz, David; Kreipp, Anika; Binnewitt, Svea Vanessa; Stegmann, Hedwig; Dittrich, Sven; Alkassar, Muhannad; Leyendecker, Sigrid (International Conference on Biomedical Technology, 2017)
Keywords: mechanics; electrophysiology; rat left ventricle; fibres; FEM.

Möglichkeiten und Perspektiven der Modellierung und Simulation - Holz, David; Duong, Minh Tuan; Martonová, Denisa; Alkassar, Muhannad; Dittrich, Sven; Leyendecker, Sigrid (Wissenschaftliche Jahrestagung der Deutschen Gesellschaft für Thorax-, Herz- und Gefäßchirurgie, 2019)

Multisite measurement of regional oxygen saturation in Fontan patients with and without protein-losing enteropathy at rest and during exercise - Schroeer, Simon; Fahlbusch, Fabian B.; Münch, Frank; Alkassar, Muhannad; Toka, Hakan R.; Rauh, Manfred; Rueffer, Andre; Cesnjevar, Robert; Dittrich, Sven; Toka, Okan; Moosmann, Julia (Pediatric Research, 2019)
Background: Protein-losing enteropathy (PLE) is a severe complication of Fontan circulation with increased risk of end-organ dysfunction. We evaluated tissue oxygenation via near-infrared spectroscopy (NIRS) at different exercise levels in Fontan patients. Methods: Assessment of multisite NIRS during cycle ergometer exercise and daily activities in three groups: Fontan patients with PLE; without PLE; patients with dextro-transposition of the great arteries (d-TGA); comparing univentricular with biventricular circulation and Fontan with/without PLE. Renal threshold analysis (<65%;<55%;<45%) of regional oxygen saturation (rSO2) was performed. Results: Fontan patients showed reduced rSO2 (p < 0.05) in their quadriceps femoris muscle compared with biventricular d-TGA patients at all time points. rSO2 in renal tissue was reduced at baseline (p = 0.002), exercise (p = 0.0062), and daily activities (p = 0.03) in Fontan patients with PLE. Renal threshold analysis identified critically low renal rSO2 (rSO2 < 65%) in Fontan patients with PLE during exercise (95% of monitoring time below threshold) and daily activities (83.7% time below threshold). Conclusion: Fontan circulation is associated with decreased rSO2 values in skeletal muscle and hypoxemia of renal tissue solely in patients with PLE. Reduced rSO2 already during activities of daily life, might contribute to comorbidities in patients with Fontan circulation, including PLE and renal failure.
CRIS-Team Scopus Importer:2019-05-21

Nonlinear fibre distribution in a finite element model of a human left ventricle for sparse and non-constant data sets - Holz, David; Duong, Minh Tuan; Kim, Myoungsic; Alkassar, Muhannad; Dittrich, Sven; Leyendecker, Sigrid (Proceedings of the 8th GACM Colloquium on Computational Mechanics, 2019)

Nonlinear fibre distribution in cardiac modelling - Holz, David; Duong, Minh Tuan; Kim, Myoungsic; Alkassar, Muhannad; Dittrich, Sven; Leyendecker, Sigrid (25th Congress of the European Society of Biomechanics, 2019)

Numerical simulation of cardiac muscles in a rat biventricular model - Duong, Minh Tuan; Ach, Theresa; Alkassar, Muhannad; Dittrich, Sven; Leyendecker, Sigrid (6th European Conference on Computational Mechanics (ECCM 6) and 7th European Conference on Computational Fluid Dynamics (ECFD 7), 2018)

Passive mechanical properties in healthy and infarcted rat left ventricle characterised via a mixture model - Martonová, Denisa; Alkassar, Muhannad; Seufert, Julia; Holz, David; Duong, Minh Tuan; Reischl, Barbara; Friedrich, Oliver; Leyendecker, Sigrid (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
During the cardiac cycle, electrical excitation is coupled with mechanical response of the myocardium. Besides the active contraction, passive mechanics plays an important role, and its behaviour differs in healthy and diseased hearts as well as among different animal species. The aim of this study is the characterisation of passive mechanical properties in healthy and infarcted rat myocardium by means of mechanical testing and subsequent parameter fitting. Elasticity assessments via uniaxial extension tests are performed on healthy and infarcted tissue samples from left ventricular rat myocardium. In order to fully characterise the orthotropic cardiac tissue, our experimental data are combined with other previously published tests in rats – shear tests on healthy myocardium and equibiaxial tests on infarcted tissue. In a first step, we calibrate the Holzapfel-Ogden strain energy function in the healthy case. Sa far, this orthotropic constitutive law for the passive myocardium has been fitted to experimental data in several species, however there is a lack of an appropriate parameter set for the rat. With our determined parameters, a finite element simulation of the end-diastolic filling is performed. In a second step, we propose a model for the infarcted tissue. It is represented as a mixture of intact myocardium and a transversely isotropic scar structure. In our mechanical experiments, the tissue after myocardial infarction shows significantly stiffer behaviour than in the healthy case, and the stiffness correlates with the amount of fibrosis. A similar relationship is observed in the computational simulation of the end-diastolic filling. We conclude that our new proposed material model can capture the behaviour of two kinds of tissues – healthy and infarcted rat myocardium, and its calibration with the fitted parameters represents the experimental data well.<br
CRIS-Team Scopus Importer:2021-04-09
Keywords: Fibrosis; Holzapfel-Ogden strain energy; Incompressibility; Myocardial infarction; Parameter fitting; Passive mechanics; Rat left ventricle

Risk factors for chylothorax and persistent serous effusions after congenital heart surgery - Raatz, Anna; Schöber, Martin; Zant, Robert; Cesnjevar, Robert; Rüffer, André; Purbojo, Ariawan; Dittrich, Sven; Alkassar, Muhannad (European Journal of Cardio-Thoracic Surgery, 2019)
OBJECTIVES: This study evaluated the various risk factors for chylothorax and persistent serous effusions (>7 days) after congenital heart surgery and developed equations to calculate the probability of their occurrence. METHODS: We performed a retrospective review of different medical databases at the University Hospital of Erlangen between January 2014 and December 2016. Full model regression analysis was used to identify risk factors, and prediction algorithms were set up to calculate probabilities. Discriminative power of the models was checked with the help of C-statistics. RESULTS: Of 745 operations on 667 patients, 68 chylothoraxes (9.1%) and 125 persistent pleural effusions (16.8%) were diagnosed. Lowest temperature [P = 0.043; odds ratio (OR) 0.899], trisomy 21 (P = 0.001; OR 5.548), a higher vasoactive inotropic score on the day of surgery (P = 0.001; OR 1.070) and use of an assist device (P = 0.001; OR 5.779) were significantly associated with chylothorax. Risk factors for persistent serous effusions were a given or possible involvement of the aortic arch during the operation (P = 0.000; OR 3.982 and 2.905), univentricular hearts (P = 0.019; OR 2.644), a higher number of previous heart operations (P = 0.014; OR 1.436), a higher vasoactive inotropic score 72 h after surgery (P = 0.019; OR 1.091), a higher central venous pressure directly after surgery (P = 0.046; OR 1.076) and an aortic cross-clamp time >86 min (P = 0.023; OR 2.223), as well as use of an assist device (P = 0.002; OR 10.281). The prediction models for both types of effusions proved to have excellent discriminative power. CONCLUSIONS: Persistent serous effusion is associated with a higher vasoactive inotropic score 72 h after surgery, an aortic cross-clamp time >86 min and elevated central venous pressure directly after surgery, which, in combination, potentially indicate cardiac stress. The developed logistic algorithm helps to estimate future likelihood.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Cardiac insufficiency; Cardiac surgery; Chylothorax; Congenital heart disease; Persistent effusions; Risk factor

Severe T-System Remodeling in Pediatric Viral Myocarditis - Fiegle, Dominik; Schober, Martin; Dittrich, Sven; Cesnjevar, Robert; Klingel, Karin; Volk, Tilmann; Alkassar, Muhannad; Seidel, Thomas (Frontiers in Cardiovascular Medicine, 2021)
Chronic heart failure (HF) in adults causes remodeling of the cardiomyocyte transverse tubular system (t-system), which contributes to disease progression by impairing excitation-contraction (EC) coupling. However, it is unknown if t-system remodeling occurs in pediatric heart failure. This study investigated the t-system in pediatric viral myocarditis. The t-system and integrity of EC coupling junctions (co-localization of L-type Ca2+ channels with ryanodine receptors and junctophilin-2) were analyzed by 3D confocal microscopy in left-ventricular (LV) samples from 5 children with myocarditis (age 14 +/- 3 months), undergoing ventricular assist device (VAD) implantation, and 5 children with atrioventricular septum defect (AVSD, age 17 +/- 3 months), undergoing corrective surgery. LV ejection fraction (EF) was 58.4 +/- 2.3% in AVSD and 12.2 +/- 2.4% in acute myocarditis. Cardiomyocytes from myocarditis samples showed increased t-tubule distance (1.27 +/- 0.05 mu m, n = 34 cells) and dilation of t-tubules (volume-length ratio: 0.64 +/- 0.02 mu m(2)) when compared with AVSD (0.90 +/- 0.02 mu m, p < 0.001; 0.52 +/- 0.02 mu m(2), n = 61, p < 0.01). Intriguingly, 4 out of 5 myocarditis samples exhibited sheet-like t-tubules (t-sheets), a characteristic feature of adult chronic heart failure. The fraction of extracellular matrix was slightly higher in myocarditis (26.6 +/- 1.4%) than in AVSD samples (24.4 +/- 0.8%, p < 0.05). In one case of myocarditis, a second biopsy was taken and analyzed at VAD explantation after extensive cardiac recovery (EF from 7 to 56%) and clinical remission. When compared with pre-VAD, t-tubule distance and density were unchanged, as well as volume-length ratio (0.67 +/- 0.04 mu m(2) vs. 0.72 +/- 0.05 mu m(2), p = 0.5), reflecting extant t-sheets. However, junctophilin-2 cluster density was considerably higher (0.12 +/- 0.02 mu m(-3) vs. 0.05 +/- 0.01 mu m(-3), n = 9/10, p < 0.001), approaching values of AVSD (0.13 +/- 0.05 mu m(-3), n = 56), and the measure of intact EC coupling junctions showed a distinct increase (20.2 +/- 5.0% vs. 6.8 +/- 2.2%, p < 0.001). Severe t-system loss and remodeling to t-sheets can occur in acute HF in young children, resembling the structural changes of chronically failing adult hearts. T-system remodeling might contribute to cardiac dysfunction in viral myocarditis. Although t-system recovery remains elusive, recovery of EC coupling junctions may be possible and deserves further investigation.
CRIS-Team WoS Importer:2021-02-19

Simulation of cardiac electromechanics of a rat left ventricle - Duong, Minh Tuan; Holz, David; Ach, Theresa; Binnewitt, Svea Vanessa; Stegmann, Hedwig; Dittrich, Sven; Alkassar, Muhannad; Leyendecker, Sigrid (Proc. Appl. Math. Mech. (PAMM), 2018)

Support Pressure Acting on the Epicardial Surface of a Rat Left Ventricle — A Computational Study - Martonová, Denisa; Holz, David; Brackenhammer, Dorothea; Weyand, Michael; Leyendecker, Sigrid; Alkassar, Muhannad (Frontiers in Cardiovascular Medicine, 2022)
The present computational study investigates the effects of an epicardial support pressure mimicking a heart support system without direct blood contact. We chose restrictive cardiomyopathy as a model for a diseased heart. By changing one parameter representing the amount of fibrosis, this model allows us to investigate the impairment in a diseased left ventricle, both during diastole and systole. The aim of the study is to determine the temporal course and value of the support pressure that leads to a normalization of the cardiac parameters in diseased hearts. These are quantified via the end-diastolic pressure, end-diastolic volume, end-systolic volume, and ejection fraction. First, the amount of fibrosis is increased to model diseased hearts at different stages. Second, we determine the difference in the left ventricular pressure between a healthy and diseased heart during a cardiac cycle and apply for the epicardial support as the respective pressure difference. Third, an epicardial support pressure is applied in form of a piecewise constant step function. The support is provided only during diastole, only during systole, or during both phases. Finally, the support pressure is adjusted to reach the corresponding parameters in a healthy rat. Parameter normalization is not possible to achieve with solely diastolic or solely systolic support; for the modeled case with 50% fibrosis, the ejection fraction can be increased by 5% with purely diastolic support and 14% with purely systolic support. However, the ejection fraction reaches the value of the modeled healthy left ventricle (65.6%) using a combination of diastolic and systolic support. The end-diastolic pressure of 13.5 mmHg cannot be decreased with purely systolic support. However, the end-diastolic pressure reaches the value of the modeled healthy left ventricle (7.5 mmHg) with diastolic support as well as with the combination of the diastolic and systolic support. The resulting negative diastolic support pressure is −4.5 mmHg, and the positive systolic support pressure is 90 mmHg. We, thereby, conclude that ventricular support during both diastole and systole is beneficial for normalizing the left ventricular ejection fraction and the end-diastolic pressure, and thus it is a potentially interesting therapy for cardiac insufficiency.

The influence of the orthotropic tissue in an electromechanical heart model - Holz, David; Martonová, Denisa; Schaller, Emely; Duong, Minh Tuan; Alkassar, Muhannad; Leyendecker, Sigrid (conference, 27th Congress of the European Society of Biomechanics, 2022)

Transmural fibre orientations based on Laplace-Dirichlet-Rule-Based-Methods and their influence on human heart simulations - Holz, David; Martonová, Denisa; Schaller, Emely; Duong, Minh Tuan; Alkassar, Muhannad; Weyand, Michael; Leyendecker, Sigrid (Journal of Biomechanics, 2023)